Living Sufism: The Transformation of Dhikr Practices in Indonesian Majelis Ta’lim - Saude Saude; Kamridah Kamridah; Saad Boulahnane (Jurnal Ilmiah Peuradeun, 2026)
While dhikr practices in majelis taklim have been widely examined, limited attention has been paid to how these practices acquire new meanings and social functions within the shifting contexts of contemporary Indonesian Muslim communities. This study examines dhikr not merely as a devotional ritual, but as a socially embedded practice through which Qur’anic engagement is transformed into ethical orientation and social relations. Using a descriptive-phenomenological approach, data were collected through in-depth interviews and participatory observation across several majelis taklim affiliated with different Sufi ṭarīqas in Palu, Indonesia. The analysis reveals four interrelated themes: variations in participants’ understanding of dhikr from rote recitation to reflective awareness; strong aesthetic engagement through rhythm and melody that deepens emotional resonance; functional dimensions of dhikr that support religious learning, emotional regulation, and moral formation; and the emergence of faith-based social capital manifested in trust, reciprocity, and cooperative networks. Conceptually, the study advances the Dynamic Reception–Conversion Model (DRCM), which explains how dhikr operates as a process linking Qur’anic reception, social mediation, and socially productive outcomes. These findings contribute to Qur’anic reception studies and scholarship on “living Sufism” by demonstrating that dhikr functions as a dynamic mechanism of social transformation, offering implications for community cohesion and faith-sensitive approaches to education and social development.